DIFFERENCE IN BRAIN ACTIVATION WITH HIGHER TASK DEMAND IN ASYMPTOMATIC ADULTS WITH AND WITHOUT AN APOE E4 ALLELE. (11th November 2018) - Whitson, H; Potter, G; Davis, S; Plassman, B; Sloane, R; Reynolds, K; Schmader, K; Welsh-Bohmer, K
Abstract: Early Alzheimer's Disease (AD) can be difficult to diagnose with traditional cognitive assessment, but brain imaging studies suggest that people with early AD exhibit an altered metabolic response to certain tasks. This proof-of-concept study was designed to determine whether differences in brain metabolic activity with increasing task demand were related to one's risk of AD. We recruited 26 individuals (age 59–72) with prior genetic testing who had normal cognitive scores and no cognitive complaints. Because the APOE e4 allele is linked to higher risk and earlier onset of AD, we included 13 APOE e4 carriers (high risk group) and a demographically balanced sample of 13 APOE e4 non-carriers (low risk group). Participants performed executive control tasks while undergoing functional magnetic resonance imaging (fMRI). Participants performed an easier version (neutral condition) followed by a harder version (stress condition) of the task. Groups did not differ in accuracy or response time in the neutral or stress condition. Next, we considered the change in brain activation between neutral and stress conditions. The low risk group exhibited larger increases in activation in right frontoparietal regions, even after adjustment for age. Age was associated with greater neutral-to-stress-condition increase in activation, but the age effect was less pronounced in the high risk group. Our hypothesis is that recruitment of supplemental networks helps support executive control in late life, and early AD may interfere with engagement of these resources. Although less activation was not associated with worse performance here, performance deterioration may occur with more challenging tasks.